Temperature-rate induced polymerization and phase separation of block copolymer toughened polymer composites. (10th November 2022) - Klingler, Andreas; Gilberg, Maurice; Wetzel, Bernd; Breuer, Ulf; Krüger, Jan-Kristian
Abstract: Understanding the genesis of polymer morphologies by phase separation is an indispensable pre-requirement to tailor the properties of polymers and composites thereof. In this work, we demonstrate the possibility to access and investigate phase separation processes of a block copolymer toughened epoxy resin under temperature-rate induced polymerization. By using (temperature-modulated optical) refractometry, the transition from a homogeneous, liquid and reactive system to the cured and demixed state is investigated. We show how different heating rates can affect the formation of particle-like domains (nodules) in terms of their composition and size, and the composition of the continuous phase (matrix). These effects are all governed by the underlying competition between a proceeding curing reaction and the mobility of the different macromolecular constituents on one hand, as well as the polymerization-induced demixing and the glass transition on the other. Graphical abstract: Image 1